Staphylococcus aureus Exotoxins Are Present In Vivo in Tampons - Schlievert, Patrick M. (American Society for Microbiology (ASM), 2010)
Staphylococcal toxic shock syndrome toxin 1 (TSST-1) is the cause of menstrual toxic shock syndrome (mTSS) associated with vaginal colonization by Staphylococcus aureus. In this pilot study, we measured TSST-1 and alpha-toxin, another exotoxin, on used tampons from four healthy women with S. aureus on tampons and from two women with tampon-associated mTSS. Tampons from all six women were sectioned into approximately 0.5-cm(3) pieces, some containing menstrual blood and some lacking menstrual blood. The pH of tampon sections with or without menstrual blood was neutral. S. aureus CFU were present in tampon sections at approximately equivalent counts (total counts were 1 × 10(8) to 2 × 10(9) CFU/tampon). TSST-1 (2 to 80 μg/tampon) and alpha-toxin (28 to 30 μg/tampon) were present only in the sections containing little or no menstrual blood (low hemoglobin density). In the tampons from TSS patients, the cytokine gamma interferon (IFN-γ) was detected only in menstrual-blood-containing sections, whereas the chemokines macrophage inflammatory protein 3α and interleukin-8 were detected in all sections. Thus, IFN-γ was being produced systemically, whereas the chemokines were being produced both locally by epithelial cells and systemically. The data show that S. aureus exotoxins can be identified in tampons ex vivo in sites with low hemoglobin density.